A Generic Conceptual Model for Risk Analysis in a Multi-agent Based Collaborative Design Environment - Ruan, J.; Qin, S. F. (Cranfield University Press, 2009)
This paper presents a generic conceptual model of risk evaluation in order to manage the risk through related constraints and variables under a multi-agent collaborative design environment. Initially, a hierarchy constraint network is developed to mapping constraints and variables. Then, an effective approximation technique named Risk Assessment Matrix is adopted to evaluate risk level and rank priority after probability quantification and consequence validation. Additionally, an Intelligent Data based Reasoning Methodology is expanded to deal with risk mitigation by combining inductive learning methods and reasoning consistency algorithms with feasible solution strategies. Finally, two empirical studies were conducted to validate the effectiveness and feasibility of the conceptual model.
Organised by: Cranfield University
Keywords: Conceptual Model; Risk; Collaborative Design